The Effect of Strong Near Surface Scattering on Seismic Imaging: Investigation Based on Resolution Analysis (Communications in Computational Physics, 2020)
In land seismic exploration, strong near-surface heterogeneities can causeserious problems in seismic data acquisition and the quality of depth imaging. By introducing random velocity models to simulate velocity fluctuations in the near-surfacelayer and using the point spread function to characterize image quality, we examinehow the scattering generated in near-surface heterogeneities can affect the subsurfaceimage. In addition to the commonly known scattering noises which lower the signalto noise ratio in seismic data, our results also reveal that intermediate scale heterogeneities generate forward scattering which forms phase or travel time fluctuations.Due to intermediate-scale uncertainty in the shallow part of the migration velocitymodel, these phase changes are carried to the target by the extrapolated wavefields,breaking the zero phase image condition at the image point. This is a primary reasonfor deteriorated image quality in regions with strong near-surface scattering. If thisintermediate-scale information can be obtained and built into the migration velocity,the subsurface image quality can be largely improved. These results can be the basis for further numerical investigations and field experiments. The proposed analysismethod can also be used to evaluate other potential methods for dealing with near-surface scattering.